Cerebrolysin for functional recovery in patients with acute ischemic stroke: a meta-analysis of randomized controlled trials - Wang ZF; Shi LG; Xu SB; Zhang JM (Dove Medical Press, 2017)
Zefeng Wang,1,* Ligen Shi,1,* Shenbin Xu,1 Jianmin Zhang1–3 1Department of Neurosurgery, Second Affiliated Hospital, School of Medicine, 2Brain Research Institute, 3Collaborative Innovation Center for Brain Science, Zhejiang University, Hangzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Cerebrolysin has been shown to have an inconsistent efficacy on functional recovery in patients with acute ischemic stroke (AIS). The present meta-analysis aims to evaluate the value of cerebrolysin and to explore the potential influencing factors. The main electronic databases, including MEDLINE, EMBASE, and the Cochrane Library, were searched. The primary outcome was functional recovery at Day 90. The secondary outcomes included mortality and adverse events. A total of 1,649 patients with AIS were pooled from six randomized controlled trials (RCTs). Cerebrolysin had no significant effect on functional recovery at Day 90 compared with the effect of placebo as shown by the modified Rankin Scale response (relative risk [RR] 1.33, 95% confidence interval [CI] 0.79–2.24, P=0.28), National Institutes of Health Stroke Scale response (RR 1.03, 95% CI 0.83–1.28, P=0.77), and Barthel Index response (RR 0.95, 95% CI 0.84–1.08, P=0.44). In safety analysis, cerebrolysin did not increase the risk of adverse events (RR 0.98, 95% CI 0.88–1.09, P=0.67), risk of serious adverse events (RR 1.20, 95% CI 0.86–1.66, P=0.29), or the mortality rate (RR 0.86, 95% CI 0.57–1.31, P=0.49). In conclusion, routine administration of cerebrolysin to patients with AIS cannot be supported by the available evidence from RCTs. Keywords: acute ischemic stroke, cerebrolysin, functional recovery, meta-analysis, randomized controlled trials